KONSEP IJTIHAD KONTEMPORER DAN IMPLEMENTASINYA DI INDONESIA - -, Muhammad Zaki Mubarak; Jalaluddin; Fathurrahman Azhari; Fahmi Hamdi (Institut Agama Islam Darul Ulum Kandangan, 2024)
As the global world develops rapidly and massively, there is a delay in Islamic law in responding to contemporary problems. In relation to Indonesia, many implementations of developments over time have resulted in new jurisprudence and institutions. This research uses normative research methods using libraries (library research) with descriptive qualitative analysis of materials. Reformulation in Islamic law is not westernization which is contrary to Islam (laws that are absolute). Recently, Muslims have shown their de facto lack of ability to meet the demands of the modern world creatively. The main things in contemporary ijtihad are, firstly, methodology, secondly operations. These two ingredients must work in synergy and integrity with each other to produce contextual fiqh. The orientation of contemporary ijtihad is not just contemporary fiqh, but also the development of dawabit al-fiqhiyyah. In the Indonesian context, the implementation of contemporary ijtihad is felt in various fields, especially law in Indonesia.. In conclusion, the implementation of contemporary ijtihad including: 1)Fatwa institutions, 2)Religious Courts, 3)Compilation of Islamic Law, 4)Office of Religious Affairs, 5)Sharia Economics, 6) Zakat Institutions, 7)Halal Labels, 8)Indonesian Fiqh, 9)Medicine, 10)Gender Equality.